OPTIMIZATION OF THE EFFICACY OF SLUDGE ULTRASONIC PRETREATMENT: A REVIEW - Tuan, Le Ngoc; Chau, Pham Ngoc (Vietnam Journal of Science and Technology, 2014)
Ultrasonication is an advanced technology in sludge pretreatment, almost thanks to hydro-mechanical shear forces created in cavitation. However, there are many factors affecting the efficacy of cavitation and consequently ultrasonic disintegration of sludge. This work aimed at selection, assessment, and indication of important parameters influencing these mentioned processes. Optimization methodologies of related parameters, the differences of optimum values as well as the similarities of effecting trends on cavitation and sludge pretreatment efficiency were specifically pointed out, including ambient conditions (temperature, external pressure), ultrasonic properties (frequency, power input, density, intensity, specific energy input, duration), and sludge characteristics (sludge type, volume of sludge, total solids concentration, pH). The research is a prerequisite for optimization of sludge ultrasonic pretreatment efficiency in lab-scale and practical application.